Storage of hybrid rough rice – Consideration of microbial growth kinetics and prediction models. (October 2016) - Atungulu, Griffiths G.; Thote, Supriya; Wilson, Shantae
Abstract: The objective of this study was to determine kinetics of mold growth on popularly grown hybrid long-grain rough rice during storage at conditions that simulate delayed drying and prolonged storage. Three long-grain hybrid rice cultivars, XL753 (2014) and CL XL745 (2014, 2015) and XL760 (2015) conditioned to four different moisture contents (MCs) (12.5%, 16.0%, 19.0%, and 21.0% wet basis) were stored in rough rice form at temperatures ranging from 10 °C to 40 °C for a period of 16 weeks. The study was repeated using rice from two consecutive crop seasons, 2014 and 2015. For all cultivars, a direct relationship between mold counts and rice MC was observed – whereas more complex trends were observed for the effect of temperature and the duration of storage on mold growth. Kinetic models including Baranyi, Weibull, Gompertz, Richard and Buchanan were successfully modified and fitted using non-linear regression and used to predict the mold counts (log10  CFU/g) for varying conditions (correlations = 0.65–0.76). The study concluded that long-grain hybrid rough rice could be stored at low MC levels (≤17%) and moderate temperatures (≤27 °C) for up to 6 weeks without any change in the mold growth profile. However, storing rice at high MC (>17%) for more than 8 weeks, especially at higher (>27 °C) temperatures should be avoided due to the potential for high mold activity leading to loss of the grain quality.